Impact of the acute national blood culture bottle shortage on the two-set blood culture rate in a single center in Japan: Insights from an interrupted time-series analysis - Tetsuji Morishita; Masao Kuwabara; Masayoshi Monji; Shin Lee; Makoto Hayashi; Hisashi Tsurumi; Hidetoshi Matsunami (Infection Prevention in Practice)
Summary: Background: In 2024, a worldwide shortage of blood culture bottles prompted efforts to mitigate its impact, including strategies to reduce blood culture orders. This study aimed to evaluate the effect of the shortage on the two-set blood culture rate in a single center in Japan. Methods: In this retrospective, single-center, observational study, blood culture data from April 2019 to January 2025 were analyzed. An interrupted time-series (ITS) analysis was performed to assess changes in the two-set blood culture rate, a key quality indicator. A Poisson segmented regression model was employed, with the shortage period as the breakpoint. Results: The ITS analysis revealed a significant immediate reduction in the level of two-set blood cultures following the shortage (risk ratio [RR]: 0.22, P < 0.01), with a subsequent significant rise in the trend (RR: 1.25, P < 0.01). The two-set blood culture rate gradually improved after the supply restriction was lifted in October, returning to pre-shortage levels by December, following an intervention by the infection control team. The total blood culture test numbers remained stable during the study period (P = 0.64). Conclusions: The blood culture bottle shortage led to a significant reduction in the two-set blood culture rate, demonstrating adaptation to shortage mitigation strategies. Monitoring the two-set blood culture rate served as an effective quality measure, enabling timely intervention by the infection control team and subsequent recovery of appropriate blood culture practices.The blood culture bottle shortage significantly reduced two-set blood culture rates. An interrupted time-series analysis showed an immediate drop, followed by recovery after an intervention. Monitoring enabled appropriate interventions to improve practices. Adapting strategies during shortages with continuous monitoring can optimize resources and patient care.